In vitro anti-inflammatory activities of Tanacetum parthenium L. extract and its major metabolite parthenolide - Baydar, Rengin; Karadağ, Ayşe Esra; Biltekin, Sevde Nur; Güzelmeriç, Etil; Demirci, Fatih (Istanbul Medipol University, 2024)
Tanacetum parthenium L. (Feverfew) is daisy-like Asteraceae plant carrying sesquiterpene lactones; used for the treatment of migraine and anti-inflamma-tory effect. This study aims to evaluate T. parthenium extract and major metabolite parthenolide for in vitro COX-1/COX-2, LOX inhibitory activity. The extract analyzed by HPTLC. To evaluate COX-1/COX-2 inhibition assays, stud-ied with commercial kits (20µg/mL concentration for extract, 5 µg/mL for par-thenolide). The major component of extract characterized as parthenolide. IC50 values for COX-1/COX-2 inhibition of extract were 10.45 and 9.81µg/mL, for parthenolide; 4.86 and 1.90µg/mL. SI values of T. parthenium extract and par-thenolide were 0.93 and 0.39. Extract showed selective COX-2 inhibitory activ-ity. The inhibition value of extract on LOX was 80% and inhibition value of par-thenolide was 41.13%. The results suggested that T. parthenium extract showed selective potential for COX-2 enzyme inhibition. To the best of our knowledge, the extract was tested with COX-1, COX-2, and LOX enzymes for the first time.
Keywords: Anti-Inflammatory; COX; Feverfew; LOX; Tanacetum Parthenium